Telisa Formation Characterization Using Seismic Acoustic Impedance Inversion in the Akasia Area of the Central Sumatra Basin - Rose Firdiany Nur Sukma; Mohammad Syamsu Rosid; Edy Wijanarko (Testing Center for Oil and Gas LEMIGAS, 2025)
The Menggala, Bekasap, and Bangko formations are the main reservoirs in many productive oil fields in the Central Sumatra Basin. However, these three formations have been extensively explored and exploited, leading to high water saturation. Meanwhile, the Telisa Formation presents an opportunity for further exploration, as studies characterizing its gas reservoir in the Central Sumatra Basin remain relatively limited. This study aims to determine the characteristics of the Telisa Formation in the Akasia Area, Central Sumatra Basin, as part of a preliminary oil and gas exploration effort. The Telisa Formation in this area is a target zone for gas reservoir characterization studies. P-impedance parameters from acoustic impedance (AI) inversion analysis are used to identify rock lithology and fluid content. The AI inversion results indicate two lithology types—shale and sandy shale—confirmed through well data. High P-impedance values, ranging from 23,000 to 27,000 (ft/s)(g/cc), are identified as shale, while sandy shale exhibits lower P-impedance values, ranging from 12,500 to 22,000 (ft/s)(g/cc). Based on well-log analysis and seismic inversion, indications of hydrocarbons in the Telisa Formation of the Akasia Area are minimal or absent. The P-impedance transformation results show that the porosity distribution in the Telisa Formation is predominantly low, with slight variations in moderate porosity, ranging from 0.02 to 0.40 v/v, classifying it as poor to good porosity.